Exploring Cultures in Primary Classrooms - Marilyn Carpenter; Lacey Grummons; Janelle Stolp; Lindsay Abbey; Meg Baker; Charlotte Streit (WOW Stories, 2012)
The Spokane Literacy Community aim to find ways to explore global literature within an international curriculum through the use of Family Story Book bags to promote an exploration of students' personal cultural identities. Each vignette provides a look into how the curriculum study unfolded in five different classrooms and how learning about personal culture set up students to better understand cultures from around the world.